Characterization of sarcoidosis at a combined rheumatology-pulmonary clinic - Schermerhorn, Megan; Seifer, Daniel; Desmarais, Julianna (Frontiers in Medicine, 2025)
ObjectiveThe treatment landscape for sarcoidosis remains poorly defined, as there is no standardized approach to management. This study aims to characterize a cohort of sarcoidosis patients in a combined rheumatology-pulmonary clinic with regard to organ involvement and medications used. To our knowledge, this will be the first published manuscript to detail such a population, providing critical insight to inform and improve the care of patients with sarcoidosis in the multidisciplinary setting.MethodsThis study was a retrospective chart review of sarcoidosis patients seen at the collaborative rheumatology-pulmonology clinic at Oregon Health & Science University during the first 5 years following the clinic’s inception (October 2018 to October 2023). Using ICD-10 diagnostic codes, 219 patient charts were identified. Of these, 37 were excluded for not meeting inclusion criteria, resulting in 182 charts eligible for data analysis. We used Excel spreadsheets to analyze our data.Results119 (65.3%) of patients in our data base had multi-organ involvement of sarcoidosis. Treatment patterns differed between patients with multi-organ sarcoidosis and those with single-organ or isolated lung/lymph node involvement. Notable differences (in prescribing) were observed among patients with cardiac and neurologic manifestations. Additionally, patients with cardiac involvement demonstrated distinct demographic characteristics, including differences in age and SRY carrier status, when compared to the broader cohort.ConclusionOur data highlights the complexity and heterogeneity of sarcoidosis seen in a combined rheumatology-pulmonary clinic. Further research is required to prospectively evaluate various pharmacologic treatment in these patients.